Translation, cross-cultural adaptation, reliability, and validation of the Italian version of the American Orthopaedic Foot and Ankle Society - MetaTarsoPhalangeal-InterPhalangeal Scale (AOFAS-MTP-IP) for the hallux - Leigheb, Massimiliano; Vaiuso, Dario; Rava, Emanuele; Pogliacomi, Francesco; Samaila, Elena Manuela; Grassi, Federico Alberto; Sabbatini, Maurizio (Acta Biomedica Atenei Parmensis, 2019)
Background and Aim of the work:  An incorrect interpretation or patients’ misunderstanding of evaluation scales can induce a mistake; therefore the real applicability of an evaluation scale should be determined by procedures that take care of cultural adaptability and not only of scientific validity. Our purpose was to translate and culturally adapt into Italian the AOFAS-MTP-IP scale for hallux, and to check its reproducibility and validity. Methods: The AOFAS-MTP-IP scale was processed for translation and checked for medical part coherence. The scale was submitted to 10 patients to verify a correct cultural adaptation. Then, the scale was submitted to 50 randomized patients operated at their hallux. Intra and inter-observer reproducibility was checked by two interviewers and a repeated interview. Short-Form-36-questionnaire for Quality of Life and Visual-Analogue-Scale for pain were also administered to perform validation analysis. The Pearson’s-Correlation-Coefficient and the Intra-Class-Correlation coefficient were calculated to analyse the scale reproducibility and validation. Results: Cultural adaptation of the translated version of the scale resulted good in terms of understandability by patients. An optimal correlation of the inter and intra-observer reproducibility was obtained. The correlation with well-known validated scales as SF-36 and VAS has shown good correlation indicating success in the validation process. Conclusions: Validation of the Italian version of the AOFAS-MTP-IP evaluation scale for hallux has been performed successfully. Therefore its use can be considered appropriate and suggested in Italian clinical practice.